2018
DOI: 10.1016/j.ajhg.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in KCNK4 that Affect Gating Cause a Recognizable Neurodevelopmental Syndrome

Abstract: Aberrant activation or inhibition of potassium (K þ ) currents across the plasma membrane of cells has been causally linked to altered neurotransmission, cardiac arrhythmias, endocrine dysfunction, and (more rarely) perturbed developmental processes. The K þ channel subfamily K member 4 (KCNK4), also known as TRAAK (TWIK-related arachidonic acid-stimulated K þ channel), belongs to the mechano-gated ion channels of the TRAAK/TREK subfamily of two-pore-domain (K2P) K þ channels. While K2P channels are well known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 41 publications
(67 reference statements)
6
99
0
Order By: Relevance
“…6 c), three (R38W, A43T, I47V) are located in M1, and two (L277M, I283V) are located in M4. Earlier studies reported that amino acid mutations in the transmembrane helices of K 2P channels would affect channel gating, which may blunt the channel responses to various types of gating commands 45 , 46 . Therefore, we hypothesized that the five amino acid mutations in the transmembrane helices of pit viper KCNK4 might have a similar effect.…”
Section: Resultsmentioning
confidence: 99%
“…6 c), three (R38W, A43T, I47V) are located in M1, and two (L277M, I283V) are located in M4. Earlier studies reported that amino acid mutations in the transmembrane helices of K 2P channels would affect channel gating, which may blunt the channel responses to various types of gating commands 45 , 46 . Therefore, we hypothesized that the five amino acid mutations in the transmembrane helices of pit viper KCNK4 might have a similar effect.…”
Section: Resultsmentioning
confidence: 99%
“…Targeted enrichment (SureSelect All Exon V.4, Agilent) used genomic DNA extracted from circulating leukocytes for the affected subject and both parents, and parallel sequencing was performed using an Illumina HiSeq2000 platform, obtaining about 70 million reads. The data analysis was performed using an in-house implemented pipeline, which mainly take advantage of the Genome Analysis Toolkit (GATK V.3.7) 47 framework, as previously reported 48,49 ). The functional annotation of variants was achieved using SnpEff and dbNSFP (V.3.0) [50][51][52] .…”
Section: Methodsmentioning
confidence: 99%
“…WES was performed using genomic DNA extracted from leukocytes of the affected subject and his parents, using the Nextera Rapid Capture Exome kit (Illumina) for library preparation, and a NextSeq500 platform (Illumina) for sequencing. WES data analysis was performed using an in-house implemented pipeline [11][12][13]. WES details and statistics are described in Supplementary Data 1 and Table S1 (Additional files).…”
Section: Molecular Analysesmentioning
confidence: 99%